Effect of a Supportive Educational Program on Self-Efficacy of Mothers with Epileptic Children - Sepideh Gholami; Tayebeh Reyhani; Mehran Beiraghi; Hamidreza Behnam Vashani (Mashhad University of Medical Sciences, 2016)
Background: In the aftermath of de-institutionalisation and the move to community management of epilepsia, mothers play an increasing role in the management of the illness. Mothers often complain of being misinformed and ill equipped to aid in the treatment. Aim: The purpose of this study was to investigate the effect of a Supportive Educational Program on self-efficacy of mothers with epileptic children. Method: This randomized controlled clinical trial was conducted on two groups of 50 mothers with epileptic children admitted to Ghaem Hospital in the city of Mashhad in 2014. Maternal self-efficacy was measured before and 6 weeks after intervention through Steffen's Revised Scale for Caregiving Self-Efficacy as the research instrument. The Supportive Educational Program was implemented for the experimental group during five 60-minute sessions with an interval of 4 days. The control group received the routine care. Data analysis was performed using SPSS software (version 11.5). Results: The mean age of mothers in the experimental and control groups were 32.8±6.9 and 32.8±6.8 years, respectively. The findings of the independent t-test revealed significant differences between the two control (47.4±15.06) and experimental (66.5±11.5) groups following the intervention (p